Anthroponyms as emotionally meaningful elements of artistic text (on material of novels of Lіna Коstenko «Marusya Chyray» and of Ulas Sumchuk «Maria») - Волкова, Ірина Вікторівна; Кордулян, Марія Іллівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
This article researched the official form of naming a person, that has a long history and represents different sides of society, economic, cultural and linguistic activity of the nation at particular historical stages. The anthroponomies in the novels of Lina Kostenko «Marusya Chyray» and of Ulas Sumchuk «Maria» were analyzed. They perform a definite stylistically function, form informational field, characterize authors’ language and style, and also become the means for expressing authors’ modality. Investigational different methods of display of expressivity of artistic text through antroponimi.